2013
DOI: 10.1140/epjc/s10052-013-2351-8
|View full text |Cite
|
Sign up to set email alerts
|

X(3872) is not a true molecule

Abstract: wave function, in the case of small binding, strongly limits the cc probability, which roughly lies in the range 7-11%, for the average experimental binding energy of 0.16 MeV and a between 2 and 3 GeV −1 . Furthermore, a reasonable value of 7.8 fm is obtained for the X(3872) r.m.s. radius at the latter binding energy, as well as an S-wave D 0 D * 0 scattering length of 11.6 fm. Finally, the S-matrix pole trajectories as a function of coupling constant show that X(3872) can be generated either as a dynamical p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(145 citation statements)
references
References 30 publications
11
132
1
1
Order By: Relevance
“…Later in Ref. [604], Coito, Rupp, and Beveren studied the X(3872) as a confined 3 P 1 cc state coupling to the almost unbound S -wave D 0D * 0 channel via the 3 P 0 mechanism. They calculated the two-component wave function for different values of the binding energy and the transition radius a, and found a significant cc component.…”
Section: Molecular Schemementioning
confidence: 99%
“…Later in Ref. [604], Coito, Rupp, and Beveren studied the X(3872) as a confined 3 P 1 cc state coupling to the almost unbound S -wave D 0D * 0 channel via the 3 P 0 mechanism. They calculated the two-component wave function for different values of the binding energy and the transition radius a, and found a significant cc component.…”
Section: Molecular Schemementioning
confidence: 99%
“…[53] and references therein). In addition, theDΛ c andD * Λ c thresholds are also located just below theD ( * ) Σ may be explained by this admixture picture of a cc core plus higher Fock components due to the coupling to the meson-meson continuum [56,[65][66][67][68][69][70][71][72][73][74][75][76][77][78]. For those interested in X, Y , and Z exotic states, a general review can be found in [56].…”
Section: Introductionmentioning
confidence: 99%
“…Problems with the two above-mentioned pictures have inspired a number of charmoniummolecular hybrid models, 6 in which the X(3872) is a quantum mechanical mixture of cc, D 0D * 0 and D + D * − components [102,103,104], where the cc component is (mostly) the χ ′ c1 . Hadronic production and radiative transitions to the ψ ′ and J/ψ are hypothesized to proceed ia the cc component and this could explain why X(3872) production properties are similar to those of the ψ ′ and its decay width to γψ ′ is larger than that for γJ/ψ (because of the closer overlap of the χ ′ c1 and ψ ′ radial wavefunctions).…”
Section: If Not Charmonium Then What?mentioning
confidence: 99%